CENTRAL ASIA DEALS WITH ITS WATER PROBLEMS: A VIEW FROM KYRGYZSTAN - KURTOV, Azhdar (CENTRAL ASIA AND THE CAUCASUS, 2004)
The region has a conflict-rich history, including on ethnic grounds. Such conflicts have also been appearing during the post-Soviet period, although in very different forms. The newly independent states of Central Asia have not found it easy to establish their sovereignty. Age-long relations among its ethnic groups were often destroyed during the process, dealing a serious blow to the interests of its nationalities and states. Where-by the initial stages of these conflicts are often not apparent to the casual observer. Until shots are fired, houses burned down, and blood spilled, politicians frequently fail to believe that such conflicts exist in their states, and society only catches on after they escalate into open warfare. At first glance, many conflicts in Central Asia can be classified as ethnic, that is, they look like clashes of diverging interests among members of different nationalities. But ethnic diversity as such is often far from the deep-rooted cause of these conflicts. In most situations, they are caused by a struggle for resources. In the past, these resources were necessary for physical survival, with wars and natural disasters being considered everyday occurrences. In today’s world, the struggle for these riches is most frequently related not so much to survival, as to the desire for a more comfortable existence.The beginning of globalization provided much greater opportunities to compare the lifestyle of different nationalities and states, especially of those living side by side. For the political elites however, the struggle for resources was always conditioned by the desire to take control over and keep a hold of political power. And in Central Asia, it was also conditioned by the political elites’ struggle for property, that is, for economic gain.